Fostering Effective Data Management Practices at Leiden University - Verhaar, Peter; Schoots, Fieke; Sesink, Laurents; Frederiks, Floor (LIBER quarterly, 2017)
At Leiden University, it is increasingly recognised that effective data management forms an integral component of responsible research. To actively promote the stewardship of all the research data that are produced at Leiden University, a comprehensive, institution-wide programme was launched in 2015, which centrally aims to encourage its researchers to carefully plan the temporal storage, long-term preservation and potential reuse of their data. This programme, which is managed centrally by the Department of Academic Affairs, and which receives important contributions from academic staff, from Leiden University Libraries, and from the University's central ICT organisation, basically consists of three parts. Firstly, a basic central policy has been formulated, containing clear guidelines for activities before, during and after research projects. The central aim of this institutional policy is to ensure that all Leiden-based research projects can effectively comply with the most common requirements stipulated by funding agencies, academic publishers, the Dutch standard evaluation protocol and the European data protection directive. As a second part of the data management programme, faculties have organised workshops and meetings, concentrating on the rationale and on the technical and organisational practicalities of effective data management in order to bring about a discipline-specific protocol. Data librarians employed by Leiden University Libraries have developed educational materials and provide training for PhDs in the principles and benefits of good data management. Thirdly, to ensure that scholars can genuinely make a reasoned selection among the many tools that are currently available, a central catalogue was developed which lists and characterises the most relevant data management services. The catalogue currently provides information about, amongst many other aspects, the organisations behind these services, the main academic disciplines which are targeted and the accepted file formats and metadata formats. The various aspects of these facilities have been classified using terminology provided by conceptual models developed by the UKDA, ANDS and the DCC. Using Leiden University's policy guidelines as criteria, the overall suitability of each service has also been evaluated. Leiden University's data management programme has a total duration of three years, and its basic objective is to offer a comprehensive form of support, in which the data management policy which is propagated centrally is complemented by various forms of assistance which ought to make it easier for scholars to adhere to this policy. The catalogue of data management services also aims to bolster the implementation of an adequate technical infrastructure, as the qualitative evaluations of the services enable policy-makers and developers to quickly establish gaps or other shortcomings within existing facilities.